Development of a smoking simulation machine to evaluate the effects of smoking on the color change of dental restorative materials - Ali Nadm Hmood; Maha Mohamed Ahmed Ebaya; Abeer El-Sayed El-Embaby (Scientific Reports)
Abstract To develop a smoking simulation machine, the study evaluated the effects of conventional and electronic cigarette smoke on the color stability of resin-based composites. Two types of nanohybrid resin-based composites were divided into two groups based on the material and subgroups according to the kind of exposure: electronic cigarettes, conventional cigarettes, and control. The exposure was by using a newly developed smoking simulation machine, and color change was the primary outcome, measured with a spectrophotometer and calculated using ΔEab. The results showed significant differences in color change were observed between the groups and subgroups (p < 0.001). Specimens exposed to conventional cigarettes exhibited more significant discoloration compared to those exposed to electronic cigarettes and control. The custom-made machine demonstrated the ability to simulate smoking conditions and their effects on dental materials. The machine provides a standard and controlled method for evaluating smoke’s effects on restorative materials, while not all materials exhibited similar reactions under the same smoking conditions. The machine impacts dental materials testing and accurately simulates the oral environment, providing insights into material performance that helps formulate materials that resist tobacco smoke, improve restoration durability with esthetics, enhance patient outcomes, and guide material selection.